2004
DOI: 10.1159/000079742
|View full text |Cite
|
Sign up to set email alerts
|

A New Model for Olfactory Placode Development

Abstract: The peripheral nervous system of vertebrate animals arises primarily from the interaction of cranial neural crest and sensory placodes. Placodes are described as thickenings of ectoderm that arise through cell division during neural tube formation. The olfactory sensory system is one component of the peripheral nervous system that arises from paired sensory placodes during development. The olfactory placodes give rise to the primary sensory neurons, support cells and basal cells of the olfactory epithelium. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 56 publications
(99 reference statements)
2
40
0
3
Order By: Relevance
“…In medaka, the differences in timing between the onset of expression of gnrh3 in the terminal nerve and gnrh1 in the hypothalamus led to the proposal that these populations do not share a common origin in the olfactory placode (Dubois et al, 2002;Parhar et al, 1998). Consistent with this hypothesis, we have found that, in zebrafish, GnRH3 cells of the terminal nerve have their origin in the cranial neural crest (Whitlock, 2004a;Whitlock, 2004b;Whitlock et al, 2003). Whether the terminal nerve arises from neural crest or the olfactory placode has been the subject of debate for the last century (Von Bartheld and Baker, 2004;Whitlock, 2004b).…”
Section: Neural Crest Origin For Gnrh3 Cells Of the Terminal Nervesupporting
confidence: 76%
“…In medaka, the differences in timing between the onset of expression of gnrh3 in the terminal nerve and gnrh1 in the hypothalamus led to the proposal that these populations do not share a common origin in the olfactory placode (Dubois et al, 2002;Parhar et al, 1998). Consistent with this hypothesis, we have found that, in zebrafish, GnRH3 cells of the terminal nerve have their origin in the cranial neural crest (Whitlock, 2004a;Whitlock, 2004b;Whitlock et al, 2003). Whether the terminal nerve arises from neural crest or the olfactory placode has been the subject of debate for the last century (Von Bartheld and Baker, 2004;Whitlock, 2004b).…”
Section: Neural Crest Origin For Gnrh3 Cells Of the Terminal Nervesupporting
confidence: 76%
“…Role of Cxcl12a/Cxcr4b signaling in olfactory placode assembly Olfactory neuron precursors initially lie in the olfactory placodal field, the region stretching along the lateral edge of the anterior neural plate (Whitlock and Westerfield, 2000;Whitlock, 2004). As development progresses, they converge to form the olfactory placode.…”
Section: Discussionmentioning
confidence: 99%
“…The diversity of cell lineages originating from the PPR cells may result from a relatively homogenous population of common progenitors, or from a number of smaller patches of cells that are biased towards a specific lineage depending on their location within the pre-placodal field Graham and Begbie, 2000;Streit, 2004;Whitlock, 2004). To address this issue, cell-fate mapping experiments examining position of cells during individual placode formation have been performed in chicken and zebrafish.…”
Section: Formation Of the Neural Tube Optic Vesicles And Lens Progenmentioning
confidence: 99%